Uncovering the hydrophobic mechanism of a novel dithiocarbamate-hydroxamate surfactant towards galena. (14th December 2021) - Liu, Sheng; Dong, Yan; Xie, Lei; Liu, Guangyi; Zhong, Hong; Zeng, Hongbo
Graphical abstract: The differential adsorption and hydrophobization of S -[(2-hydroxyamino)-2-oxoethyl]- N, N -dipropyl dithiocarbamate (HAPTC) towards galena and sphalerite, and HAPTC's selective flotation separation of galena from its mixture with sphalerite. Highlights: S -[(2-hydroxyamino)-2-oxoethyl]- N, N -dipropyl dithiocarbamate was used as PbS collector. In situ AFM observed a denser adsorption of HAPTC on galena than sphalerite. AFM force revealed HAPTC's selective hydrophobization to galena versus sphalerite. HAPTC achieved a selective flotation separation of galena from sphalerite at pH 9. Both dithiocarbamate and hydroxamate groups of HABTC anchored on galena. Abstract: Flotation separation is determined by chemical additives which can enlarge the hydrophobicity difference of minerals. Herein, S -[(2-hydroxyamino)-2-oxoethyl]- N, N -dipropyl dithiocarbamate (HAPTC) was firstly developed for the flotation separation of galena and sphalerite. In situ AFM imaging elucidated a much stronger adsorption affinity of HAPTC towards galena (PbS) than that to sphalerite (ZnS) at pH 6.2 and 9.0. The AFM force findings and the extended DLVO theory analyses indicated that HAPTC adsorption promoted the hydrophobicity of galena surface more significantly than that of sphalerite. The micro-flotation results showed that HAPTC achieved a selective flotation separation of galena against sphalerite at pH around 9.0. FTIR and XPS uncovered that both dithiocarbamate and hydroxamate groups in HAPTC participated in the bonding interaction with Pb sites on galena surface with the formation of Pb-S and Pb-O bonds. The results provide implications on developing novel reagents, and the fundamental understanding of their adsorption and hydrophobization to minerals at nanoscale.